2014
DOI: 10.1001/jamaneurol.2013.4835
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofTMEM106BPolymorphism on Functional Network Connectivity in AsymptomaticGRNMutation Carriers

Abstract: rontotemporal dementia (FTD) is a neurodegenerative disorder in which behavioral abnormalities, language impairment, and executive function deficits represent the most typical clinical features. 1,2 One of the most common causes of inherited FTD is the loss-of-function mutations within the granulin (GRN) gene (OMIM 138945). 3,4 More than 60 different pathogenetic mutations have been identified so far (http://www.molgen.ua.ac.be/FTDmutations). GRN mutations lead to FTD with TDP-43 inclusions 5 and have a wide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…Conversely, aGRN+ group was better classified by local connectivity measures (especially fALFF) with a discrimination pattern characterized by a widespread connectivity decrease in parietal and posterior associative areas, with a well-structured increased connectivity in prefrontal regions. Especially for aGRN+ and in line with literature data [16,20,36], the concept that red-yellow areas could be considered as increased connectivity was more plausible. Finally, fALFF index was the only measure with high (>80%) discriminative power in both comparisons (FTD-GRN+ versus oHC and aGRN+ versus yHC).…”
Section: Classifier Performancesupporting
confidence: 76%
See 3 more Smart Citations
“…Conversely, aGRN+ group was better classified by local connectivity measures (especially fALFF) with a discrimination pattern characterized by a widespread connectivity decrease in parietal and posterior associative areas, with a well-structured increased connectivity in prefrontal regions. Especially for aGRN+ and in line with literature data [16,20,36], the concept that red-yellow areas could be considered as increased connectivity was more plausible. Finally, fALFF index was the only measure with high (>80%) discriminative power in both comparisons (FTD-GRN+ versus oHC and aGRN+ versus yHC).…”
Section: Classifier Performancesupporting
confidence: 76%
“…As previously described [16,20], all preprocessing steps were carried out using Advanced Data Processing Assistant for resting-state fMRI (DPARSFA) (http://rfmri.org/DPARSF) [27] which is based on Resting-State fMRI Data Analysis Toolkit (REST, http://www.restfmri.net) [28] and Statistical Parametric Mapping (SPM8) (http://www. fil.ion.ucl.ac.uk/spm).…”
Section: Mri Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent work demonstrated several associations between neuroanatomical structure and single nucleotide polymorphisms in sporadic forms of FTD and ALS. 36 Others have suggested that TMEM106B is a modifier of functional connectivity in FTD 37 and that cognitive reserve mechanisms such as education may provide regionally protective modifiers of neuroanatomic structure. 38 Other potential caveats to consider in the current study are related to our study population.…”
mentioning
confidence: 99%